THE TRANSFORMATION OF SANCTIONS IN THE CURRENT SYSTEM OF INTERNATIONAL ECONOMIC RELATIONS - Yurynets, Oksana; Melnyk, Olga; Bulatova, Olena (Current Problems of Sustainable Development, 2026)
Based on the results of a critical analysis of existing approaches to determining the economic impact of sanctions, the scope and nature of sanctions (trade, financial, personal, military, and specific) have been identified. It is argued that the proliferation of sanctions in the current context of global economic development creates new challenges for the development of international business, worsens macroeconomic indicators of countries’ development, contributes to the deepening of inequality, and so on. The rapid increase in the use of economic coercion tools has resulted from a significant intensification of competition among states. Based on the analysis of The Global Sanctions Data Base (GSDB) the characteristic features of the transformation of sanctions in the global economy were identified according to relevant criteria (purpose, nature of application, scope, impact), and the evolution of sanction types was revealed (from broad-based economic coercion tools to a narrower spectrum (sectoral nature, visa restrictions, specific individuals, etc.). It has been determined that sanctions do not lead to a rapid change in a country’s political course; however, they create a cumulative negative effect that gradually weakens the country’s economic potential and its capacity for long-term development (technological lag, constraints on production modernization and innovative development, declining productivity, and the outflow of skilled personnel). It has been demonstrated that sanctions are significantly less effective against undemocratic regimes. Authoritarian regimes can adapt to sanctions pressure and using it to mobilize domestic support. An analysis of the application of sanctions against Russia has revealed a number of mechanisms for circumventing sanctions restrictions that undermine the effectiveness of the sanctions regime imposed on the aggressor country: adaptation of foreign capital to the conditions of the aggressor’s war economy, transit through third countries, shadow fleet, digital channels, and nominal ownership of real estate. It has been determined that the increasing complexity of the global sanctions’ architecture intensifies the requirements for sanctions compliance for international businesses and the conduct of relevant investigations. To enhance the effectiveness of the sanctions imposed and prevent their evasion, it is necessary to synchronize the efforts of intelligence and financial authorities at the international level.
Keywords: sanctions; international norms; international business; international consulting; EU; Ukraine